Exploring Postgraduate Students' Of Negotiated Curriculum - Nur Safura Binti Ab. Ghaffar; Nur Hidayah Md Yazid; Mumtaz Najiah Musa; Nur Syarah Farhah Mohd Noor; Nurul Munirah Azamri; Faizah Abd Majid (Elsevier- Science Direct, 2024)
Procedia - Social and Behavioral Sciences Volume 123, 20 March 2014, Pages 182-188